Delay in seeking healthcare for pneumonia and associated factors among mothers/caregivers of children aged 2-59 months in public health facilities in Nekemte town, Ethiopia - Dereje Temsesgen; Berhanu Wordofa; Tewodros Tesfaye; Werku Etafa (BMC, 2023)
Abstract Background Pneumonia is the most significant infectious disease and the predominant cause of death among under-five children (U5C) in low- and middle-income countries. It is the second leading cause of death in Ethiopia. Delay in seeking healthcare is one of the contributing factors to pneumonia-associated mortality. There is a limitation to the study aimed at identifying health-seeking behavior and risk factors in the western part of Ethiopia. The study aimed to determine the level of delay in seeking healthcare for pneumonia and associated factors among caregivers of U5C in public health facilities in Nekemte town, Ethiopia. Methods A health facility-based cross-sectional study was conducted from 1st March to 5thApril, 2022 using a structured interviewer-administered questionnaire to collect data from 410 caregivers of children aged 2-59 months. We used a systematic sampling technique for collecting the data. For analysis, data were entered into Epi Data version 4.6 and exported to SPSS version 25. Binary logistic regression was used to identify the associated factors of delay in seeking healthcare for pneumonia at a p-value < 0.05 using a 95% confidence interval (CI) in multivariable logistic regression. Results A proportion of delays in seeking healthcare for pneumonia among children aged 2-59 months is 62.2%. Rural residence (AOR = 2.77, CI:2.48-5.17), child aged ≥12 months (AOR = 5.4,95%CI:4.17-7.20), monthly income < 1000 Ethiopian birr (AOR = 6.11,95%CI:2.16-17.26,), not using health insurance (AOR = 8.93,95%CI:5.43-14.68), use of self-medication (AOR = 10.97,95%CI:1.85-65.3), poor knowledge (AOR = 4.63,95%CI: 1.35-15.9), perceiving illness due to pneumonia as mild (AOR = 14.97,95%CI:9.76-22.9) and no previous admission history (AOR = 2.85,95%CI:1.77-4.56) were significant factors for delay in seeking healthcare for pneumonia among children aged 2-59 months. Conclusion The study emphasizes that caregivers' delay in seeking healthcare for pneumonia is high. Creating caregivers' awareness or providing adequate health education to develop early healthcare-seeking behavior and encouraging caregivers to use health insurance is essential.